The global rules of art : the emergence and divisions of a cultural world economy - Buchholz, Larissa (Princeton University Press, 2022)
A trailblazing look at the historical emergence of a global field in contemporary art and the diverse ways artists become valued worldwidePrior to the 1980s, the postwar canon of "international" contemporary art was made up almost exclusively of artists from North America and Western Europe, while cultural agents from other parts of the world often found themselves on the margins. The Global Rules of Art examines how this discriminatory situation has changed in recent decades. Drawing from abundant sources--including objective indicators from more than one hundred countries, multiple institutional histories and discourses, extensive fieldwork, and interviews with artists, critics, curators, gallerists, and auction house agents--Larissa Buchholz examines the emergence of a world-spanning art field whose logics have increasingly become defined in global terms.Deftly blending comprehensive historical analyses with illuminating case studies, The Global Rules of Art breaks new ground in its exploration of valuation and how cultural hierarchies take shape in a global context. The book's innovative global field approach will appeal to scholars in the sociology of art, cultural and economic sociology, interdisciplinary global studies, and anyone interested in the dynamics of global art and culture.
Keywords: Art -- Marketing.; Art, Modern -- 20th century -- Economic aspects.; Art, Modern -- 21st century -- Economic aspects.; Art and globalization.; Art -- Commercialisation.; Art -- 20e siècle -- Aspect économique.; Art -- 21e siècle -- Aspect économique.; Art et mondialisation.; art market.; ART / Business Aspects.; Art and globalization; Art -- Marketing; Art, Modern -- Economic aspects; The arts: general issues.; Art and Design.; 1900-2099; Andy Warhol.; Art Basel.; Art Express.; Art Journal (College Art Association journal).; Art auction.; Art critic.; Art criticism.; Art department.; Art for art's sake.; Art group.; Art history.; Art methodology.; Art movement.; Artforum.; Artnet.; Artprice.; Auction.; Capital control.; Career.; Central bank.; Commercial art.; Competition (economics).; Competitive landscape.; Contemporary art.; Core business.; Cultural Revolution.; Cultural capital.; Cultural imperialism.; Curator.; Currency.; Deterritorialization.; Documenta.; Economic capital.; Economic globalization.; Ethnoscape.; Externality.; Fluxus.; General Agreement on Tariffs and Trade.; Geopolitics.; Global Exchange.; Global Finance (magazine).; Global Leadership.; Global Map.; Global administrative law.; Global city.; Global field.; Global imbalances.; Global issue.; Global justice.; Global saving glut.; Global strategy.; Global studies.; Globalism.; Globality.; Globalization.; Headline.; Imperialism.; India Art Fair.; Infrastructure.; Institution.; International Competition Network.; International Monetary Fund.; International Style (architecture).; International economics.; International law.; International monetary systems.; International organization.; International relations.; Internationalization.; Jeff Koons.; Kunsthalle.; Kunstmuseum Basel.; Land art.; Law of war.; Market liquidity.; Mercantilism.; National symbol.; Nationalization.; New International Economic Order.; Policy.; Pop art.; Principles (retailer).; Protectionism.; Public international law.